The Molecular Evolutionary Patterns of the Insulin/FOXO Signaling Pathway. (January 2013) - Wang, Minghui; Wang, Qishan; Wang, Zhen; Wang, Qingping; Zhang, Xiangzhe; Pan, Yuchun
The insulin/insulin growth factor-1 (IGF1)/FOXO (IIF) signal transduction pathway plays a core role in the endocrine system. Although the components of this pathway have been well characterized, the evolutionary pattern remains poorly understood. Here, we perform a comprehensive analysis to study whether the differences of signaling transduction elements exist as well as to determine whether the genes are subject to equivalent evolutionary forces and how natural selection shapes the evolution pattern of proteins in an interacting system. Our results demonstrate that most IIF pathway components are present throughout all animal phyla investigated here, and they are under strong selective constraint. Remarkably, we detect that the components in the middle of the pathway undergo stronger purifying selection, which is different from previous similar reports. We also find that the dN /dS may be influenced by quite complicated factors including codon bias, protein length among others.